(untitled) (Victoria Journal of Management, 2025)
Financial inclusion, broadly defined as the provision of affordable and appropriate f inancial services, is increasingly recognized as a critical driver of tourism development, particularly in developing countries like Nepal. However, empirical evidence specific to Pokhara, Nepal’s major tourism hub, remains limited. This study investigates the impact of financial inclusion on tourism development in Pokhara, focusing on three dimensions – access, quality, and usage of financial services. A descriptive and analytical research design was employed. Primary data were collected through a structured questionnaire from 160 tourism-related entrepreneurs, including hotels, restaurants, tour operators, transportation services, and local artisans, using purposive sampling. Data were analyzed using descriptive statistics, exploratory factor analysis (EFA), correlation, and multiple regression analysis to assess relationships between financial inclusion and tourism development. Results indicate generally positive perceptions toward financial inclusion, with higher ratings for quality and usage compared to access. Correlation analysis revealed significant positive associations between all financial inclusion dimensions and tourism development. Regression analysis demonstrated that quality (β = 0.400, p < 0.001) and usage (β = 0.201, p < 0.001) significantly predict tourism development, while access showed no significant effect. The model explained 48.3% of the variance in tourism development. The study concludes that financial inclusion positively contributes to tourism development in Pokhara, with quality and usage emerging as critical drivers, whereas access alone is insufficient. Policymakers and financial institutions should prioritize enhancing service quality, tailoring products to entrepreneurs’ needs, and promoting active usage of financial tools – especially digital services – to foster tourism development in Nepal.